Japanese prints : - Michener, James A. (The Honolulu Academy Arts, 1959)
This book deals with what have been called the magnificent scraps of paper the woodblock prints of Japan, and with their modern successors the creative prints, of which more later. The proper name for the traditional prints reveals their meaning: ukiyo-e, pictures of the passing world, and the three examples which open this easy, prints 2, 3 and 4 have been especially chosen to illustrate certain basic aspects of this enchanting art.